2010
DOI: 10.1002/jcb.22886
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the p38 MAPK/Akt/ERK1/2 signal pathways is required for the protein stabilization of CDC6 and cyclin D1 in low‐dose arsenite‐induced cell proliferation

Abstract: Arsenic trioxide (ATO) is a first-line anti-cancer agent for acute promyelocytic leukemia, and induces apoptosis in other solid cancer cell lines including breast cancer cells. However, as with arsenites found in drinking water and used as raw materials for wood preservatives, insecticides, and herbicides, low doses of ATO can induce carcinogenesis after long-term exposure. At 24 h after exposure, ATO (0.01-1 µM) significantly increased cell proliferation and promoted cell cycle progression from the G1 to S/G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…Finally, in contrast to ATRA, arsenic trioxide which induces apoptosis in APL does not affect miR-181a/b expression and RASSF1A protein. This correlates with the finding that arsenic trioxide does not donwregulate cyclin D1 protein (50). Based on these findings, we claim RASSF1A as an important factor in the granulocytic differentiation, which prevents cyclin D1 accumulation, cell cycle progress and promotes differentiation upon ATRA-treatment in APL blasts.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, in contrast to ATRA, arsenic trioxide which induces apoptosis in APL does not affect miR-181a/b expression and RASSF1A protein. This correlates with the finding that arsenic trioxide does not donwregulate cyclin D1 protein (50). Based on these findings, we claim RASSF1A as an important factor in the granulocytic differentiation, which prevents cyclin D1 accumulation, cell cycle progress and promotes differentiation upon ATRA-treatment in APL blasts.…”
Section: Discussionsupporting
confidence: 87%
“…In the identified pan-cancer FFLs, CCND1 and JUN are drug targets of ATO, which span three pan-cancer FFLs (Figure 6). ATO is an antagonist of CCND1, which has been validated in many cancers, such as bladder cancer [62], breast cancer [63], kidney cancer [64], liver cancer [65] and NSCLC [66]. In this study, we found that CCND1 was upregulated in most of the tumor types (Figure 6).…”
Section: Resultsmentioning
confidence: 53%
“…Apoptosis is induced through many ways including the disequilibrium of apoptotic/anti-apoptotic BCL 2 family members [43], reactive oxidative species generation [44], cytochrome C release, loss of mitochondrial transmembrane potential, inactivation of NF-kB [45,46], activation of caspases [47], activation of MAPK pathways [48,49], as well as activation of Rho GTPases pathway [9]. Among these mechanisms, the two best-characterized Rho family members Cdc42 and Rac1, have been found to play a critical role in regulating cellular processes, including cell proliferation, migration, differentiation, and apoptosis [11,50].…”
Section: Liu Et Al: Protective Role Of Neuroglobin In Rat Cerebellarmentioning
confidence: 99%